Körpülü kranın metalkonstruksiyasının korroziyaya davamlılığının tədqiqi (kran metalkonstruksiyasının atmosfer korroziyası prosesinin modelləndirilməsi, kran metalkonstruksiyasının korroziya yorulmasının tədqiqi) - Süleymanlı, Ayşən; Yaqiyev, Elxan (My University, 2024)
A schematic model for the accumulation of fatigue damage in the metal structure of a lifting machine exposed to an aggressive environment has been proposed, and the stages of fatigue crack formation have been examined. A model has been proposed to determine the depth indicators of atmospheric corrosion, taking into account the structural features of the lifting machine. In this model, all parameters characterizing the impact of the aggressive environment are considered. The stress-strain state of the truss-type metal structure shafts of the lifting machine, which is exposed to surface corrosion, has been investigated.
Research on the corrosion resistance of the metal structure of a bridge crane (Modeling the atmospheric corrosion process of a crane metal structure, Research on the corrosion fatigue of a crane metal structure)
Keywords: Types of corrosion; Crane metal structure